2018
DOI: 10.1177/1076217517750700
|View full text |Cite
|
Sign up to set email alerts
|

England Policy in Gifted Education: Current Problems and Promising Directions

Abstract: This article presents and analyzes policies in identification and provisions in England with respect to gifted education. England has developed a national policy to provide services to identified students. Surveys and interviews with teachers illustrate how implementation of both identification and provision policy elements were handled. Although policy evaluation was conducted by an external ministry agency, it appears to have had little impact on practice. The article suggests that policy implementation, if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…On the contrary, in 2012 in England, it was determined that the rules and regulations regarding gifted and talented students are not coherently implemented (Office for Standards in Education, Children’s Services and Skills, 2013). Several studies on the issue of educating gifted students in England have presented critical opinions, stating that calling a child gifted or talented, as recently popularized by the policy of the Government of Great Britain, may be perceived as a sign of harmful obsessions, wherein children are categorized and labeled in accordance with specific cultural and social concepts (Heller-Sahlgren, 2018; Koshy et al, 2018; Koshy & Pinheiro-Torres, 2013; Lambert, 2010).…”
mentioning
confidence: 99%
“…On the contrary, in 2012 in England, it was determined that the rules and regulations regarding gifted and talented students are not coherently implemented (Office for Standards in Education, Children’s Services and Skills, 2013). Several studies on the issue of educating gifted students in England have presented critical opinions, stating that calling a child gifted or talented, as recently popularized by the policy of the Government of Great Britain, may be perceived as a sign of harmful obsessions, wherein children are categorized and labeled in accordance with specific cultural and social concepts (Heller-Sahlgren, 2018; Koshy et al, 2018; Koshy & Pinheiro-Torres, 2013; Lambert, 2010).…”
mentioning
confidence: 99%
“…This programme also operated within the awareness that geography plays an important role in the academic access and the ability of students to realise latent talents. For example, in targeting urban areas, it acknowledged that gifted students may "have been hibernating in social situations, given neither recognition nor encouragement" (Casey, Portman Smith and Koshy, 2011 [51]; Koshy, Smith and Brown, 2017 [147]).…”
Section: Resourcing Gifted Educationmentioning
confidence: 99%
“…Research has shown that the involvement of parents and communities in the learning process of their children plays a prominent role in their overall success and well-being in schools. Reviews of international evidence on parental involvement showed that "good parenting has a significant impact on children's achievement and adjustment, evident across all social classes and all ethnic groups", including for gifted students (Koshy, Smith and Brown, 2017 [147]). Increasingly, school-family partnerships and community-centred approaches are recognised as highly efficient in supporting all students, including gifted ones, and help them achieve their potential (Matthews and Menna, 2003[193]; OECD, 2019 [194]).…”
Section: Engagement With Parents and Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Practices for the education of gifted students continue to develop around the world and many countries' attention on gifted education is increasing (Koshy, Smith and Casey, 2018;Kronborg, 2018;Reid, 2015). The researches in the field display that acceleration, enrichment and differentiation practices used in educational services for gifted students, have increased the academic achievement of gifted students (Colangelo, Assouline and Gross, 2004;Lee, Olszewski-Kubilius and Peternel, 2010;Umar and Reis, 2014).…”
mentioning
confidence: 99%